Knowledge, belief and barriers to adult influenza and pneumococcal vaccination among primary care doctors in Sarawak - Wong, Samuel Leong Kheng; Muthupalaniappen L,; Tie ST, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Adult influenza and pneumococcal vaccinations are grossly underutilized although there is clear benefit in reducing mortality and morbidity among those at risk. The aim of the study was to assess primary care physician’s knowledge on adult influenza and pneumococcal vaccinations, their beliefs and barriers to vaccination. A cross-sectional study using self-administered questionnaires was conducted at eight primary care centres in Kuching, Sarawak. A total of 108 primary care physicians participated in this study. Median age of participants was 29 years (IQR 4.0). The median knowledge score for influenza vaccine was 9 (IQR 3) and for pneumococcal vaccine was 8 (IQR 4). Female participants scored higher compared to their male counterparts for influenza and pneumococcal vaccines (P = 0.005 & 0.007). The highest percentage of correct responses for influenza vaccination was for side effects (75.3%) while the lowest was for contraindications (9.3%). The highest percentage of correct responses for pneumococcal vaccination was for side effects (69.1%) while the lowest was for advocated target groups (6.2%). Most participants believed that pneumococcal and influenza vaccines were safe (92.8 & 99%) and beneficial for patients (89.7 & 93.8%). Cost of influenza and pneumococcal vaccines (94.8% & 96.9%) and their availability (86.6% & 89.7%) were the main barriers to prescribing them. Primary care physicians in the public sector have moderate knowledge of both adult vaccinations. Areas of knowledge paucity and barriers need to be addressed to ensure a more comprehensive health care delivery to the aging Malaysian population.